SP0111 Calcinosis, Lipodystrophy and Other Pediatric Features. (9th June 2015) - Feldman, B.M.
Abstract : Patients with juvenile idiopathic inflammatory arthritis (JIIM) usually have the dermatomyositis phenotype (JDM). As such, children present much like adults with dermatomyositis with some notable differences. This talk will focus on similarities and differences between adult and childhood dermatomyositis, with a special focus on the absence of malignancy as an etiological factor, as well as the course, prognosis, autoantibodies, and clinical features of JDM such as lipodystrophy and calcinosis. Disclosure of Interest: None declared